Smoothed particle hydrodynamics and modal reduction for efficient fluid–structure interaction. Issue 4 (4th July 2018) - Schörgenhumer, Markus; Humer, Alexander
ABSTRACT: From wind turbines to capillary blood flow, problems of fluid–structure interaction occur across different scales of length and time. Owed to the multiple scales involved, the inherent complexity of coupled fluid and structural dynamics requires advanced numerical methods for the computational analysis. The proposed method relies on the coupling of modally reduced flexible multibody systems with fluids represented by the smoothed particle hydrodynamics method. A reduced-order basis is employed to describe small flexible deformation of a structural component relative to its large rigid body motion that is represented by a body-fixed frame. An efficient evaluation of the surface deformation of the bodies involved is a vital ingredient for the coupling. Conventional approaches suffer from the drawback of flexible deformation being represented in a body-fixed local frame. The generalized component mode synthesis, in which the total displacement is interpolated, mitigates this computational limitation. The linear relation between generalized coordinates and the total displacement allows the coupling forces to be evaluated within the parallel fluid framework. Only the reduced set of equations of motion is solved on the solid side using an implicit time integration scheme with possibly large time-steps, whereas the particle-based fluid simulation relies on a fast explicit scheme.